Multicultural Representation in Global Language Textbook Used by Indonesian EFL Learners - Reffi Sabillawati; Kristian Adi Putra (Yayasan Keluarga Guru Mandiri, 2023)
Most previous studies find that global textbooks for EFL learners are still unbalanced and contain multicultural values. At the same time, students have to be able to communicate with people from different cultures. For this reason, this discourse study compares multicultural depicted in a global language textbook endorsed by Cambridge University Press entitled English in Mind Second Edition and used by Indonesian EFL learners at the junior high school level. This study implemented qualitative analysis and was informed by a critical discourse approach. It unearths what multicultural values are represented in the textbook regarding Byram’s intercultural communicative competence (2013), Yuen's cultural parameters (2011), and Kachru's three concentric circles (1985). The finding shows that in three concepts adopted in the research, the global textbook multicultural values are unbalanced, presented through the book activity, text, and images. The textbook dominates inner circle aspects even though it is used in Indonesia as expanding circle country. Based on the finding, it highly recommends that the textbook writers give the balancing multicultural value in global textbooks primarily used in expanding circle country. This study aims to help teachers increase multicultural creativity aspects for students and develop cultural and language critical awareness for textbook writers. It aims to engage EFL learners more responsive to multicultural values in pedagogical or in education practices.